Comparative Study between Closed and Open Drain after Emergency Laparotomy - Rabah Ali Hussein; Jameel I. Azzawi; Basim Ghaib Hussein (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Drain routinely used after laparotomy to drain any intraperitoneal collections, and to drain thefluid or blood in abdomen after operations.Methods: prospective study for acute abdomen patients undergoing laparotomy in Department of Generalsurgery. Samarra General Hospital for open and closed drain.Result: In our study 30 case of emergency operations with open drain and 30 case of closed drain are placedand comared.Conclusions: The incidence of infection, pain, hospital stay, post-operative morbidity not obviously